Factors influencing advertising from an islamic perspective: case of Wangsa Maju / Alya Johari - Johari, Alya (2016)
This project paper's main objective is to study what are the factors that can influence advertising from an Islamic perspective in Wangsa Maju. The independent variables for the project paper are culture factors, control factors and emotion factors. The sample of this study will comprise of 100 respondents of teachers at SMK Wangsa Maju where a set of questionnaire will be distribute to each of the respondents. This project paper also will use a multiple regression analysis; correlations analysis, and descriptive analysis and will be conducted in SPSS 22 computer software.